Factors Associated with the Development of Chronic Pain after Surgery for Breast Cancer: A Prospective Cohort from a Tertiary Center in the United States. Issue 1 (13th November 2013) - De, Gildasio S.; Chang, Ray; Khan, Seema A.; Hansen, Nora M; Khan, Jamil H.; McCarthy, Robert J.; Apkarian, Apkar V
Abstract Chronic pain has been shown to affect up to 60% of patients undergoing surgery for breast cancer. Besides younger age, other risk factors for the development of chronic pain have not been consistent in previous studies. The objective of the current investigation was to detect the prevalence and risk factors for the development of chronic pain after breast cancer surgery by examining a patient population from a tertiary cancer center in the United States. The study was a prospective observational cohort study. Subjects were evaluated at least 6 months after the surgical procedure. Subjects responded to the modified short form Brief pain inventory and the short form McGill pain questionnaire to identify and characterize pain. Demographic, surgery, cancer treatment, and perioperative characteristics were recorded. Propensity matching regression analysis were used to examine risk factors associated with the development of chronic pain. 300 patients were included in the study. 110 reported the presence of chronic pain. Subjects with chronic pain reported median (interquartile range [IQR]) rating of worst pain in the last 24 hours of 4 (2–5) and a median (IQR) rating on average pain in the last 24 hours of 3 (1–4) on a 0–10 numeric rating scale. Independent risk factors associated with the development of chronic pain were age, OR (95% CI) of 0.95 (0.93–0.98) and axillary lymph node dissection, 7.7 (4.3–13.9) but not radiation therapy, 1.05(0.56–1.95). After propensity matching for confounding covariates, radiation was still not associated with the development of chronic pain. Chronic pain after mastectomy continues to have a high prevalence in breast cancer patients. Younger age and axillary lymph node dissection but not radiation therapy are risk factors for the development of chronic pain. Preventive strategies to minimize the development of chronic pain are highly desirable.